Pemikiran Ibn Taymiyyah terhadap Aliran Filsafat Idealisme dan Realisme serta Relevansinya terhadap Pemikiran Pendidikan Islam - Abdullah Helmy, Helmy; Aksaril Huda Ritonga, Mhd; Parhan, Muhamad; Warasy Batula, Abu; Hikmatiar, Zidny (Zawiyah: Jurnal Pemikiran Islam, 2026)
This article examines Ibn Taymiyyah’s epistemology as a philosophical foundation for reconstructing contemporary Islamic educational paradigms. Arising from concerns over the fragmentation between textual memorization, the neglect of empirical reality, and the penetration of Western idealism and realism into modern curricula, this study seeks to offer an integrative framework grounded in the triad of revelation, reason, and fiṭrah. Through a literature review employing a comparative–philosophical approach to Ibn Taymiyyah’s classical writings and relevant modern scholarship, the study maps his critiques of idealist and realist philosophies, including his rejection of metaphysical universals, the essence–existence distinction, and reliance on Aristotelian syllogism. The findings indicate that Ibn Taymiyyah’s epistemology affirms a theistic realism rooted in sensory experience, tawātur, and the innate disposition (fiṭrah) as sources of epistemic certainty, alongside a preference for analogical reasoning (qiyās tamthīl) that is more contextual and applicable than formal deduction. The study concludes that Ibn Taymiyyah’s epistemic structure holds direct relevance for curriculum design, fiṭrah-based pedagogy, knowledge integration, and the strengthening of spiritual character in the digital age. Thus, Taymiyyan epistemology offers a conceptual foundation for an Islamic educational model that is critical, empirical, and rooted in revelatory values.